Optimization of seed power for suppression of stimulated Raman scatting in all-fiber amplifiers. (24th January 2019) - Zhang, Jingpu; Chen, Xiaolong; Bai, Gang; He, Yu; Liu, Kai; He, Bing; Zhou, Jun
Abstract: In this paper, the influence of seed power on a few-mode all-fiber amplifier is analyzed theoretically and experimentally. Numerical simulation results gave an optimized seed power for this amplifier considering three factors which are usually important in high-power fiber lasers: optic-to-optic efficiency, Raman ratio and output power. A 3.02 kW light with a good beam quality ( M 2 1.7) has been obtained with an injection seed power of 300 W, and the intensity of Raman light was 20 dB below the signal light in the spectrum. In experiments with other injected seed powers, the output characteristics were degraded to different degrees, in agreement with the theoretical results.